The Influence of Competency, Discipline, and Workload on Employee Performance through Job Satisfaction: A Case Study : JEL Classification: M53, J24, D23, M12, J28 - Suyuthi, Nurmadhani Fitri; Fitriani, Mustaani; Yusri, Yusri; Samayo, M. Rio (Newinera Publisher, 2025)
This study examines the interference of competency, discipline and workload on the performance in a regulated professional services organization namely the Public Appraisal Services Office (KJPP) Satria Setiawan dan Rekan located in Indonesia. With the current performance expectations in service settings being more complex than ever before, it is important to spell out the dynamics behind the forces of productivity. Based on that, quantitative method, structural equation modelling using Smart PLS 4.0 and the study sample containing 75 certified appraisers registered in the Indonesian Ministry of Finance were employed. Findings show how competency, discipline and workload are having significant effects towards job satisfaction and significantly to the extent that the employee performance is affected positively. More importantly, competency plays a full mediatorship role through job satisfaction, which is not manifested in the case of discipline and workload. These data indicate that technical skills and structure of tasks are not enough to determine the outcome of a performance, rather there is another central psychological process job satisfaction that mediates or diminishes the effect of the foregoing processes. Therefore, on the managerial level, the strategy of human capital will have to go beyond the functional training and adherence protocols to invoking embodied experience and emotional commitment in the employees. Job satisfaction should be viewed as an organizational strategic priority by the organizations trying to ensuring sustainable performance through use of job satisfaction in competency development, work load design and cultural reinforcement.